Alfred binet: Charcot’s pupil, a neuropsychologist and a pioneer in intelligence testing Alfred Binet: Pupilo de Charcot, neuropsicólogo e pioneiro nos testes de inteligência - Teive H.A.G. (2017)
© 2017, Associacao Arquivos de Neuro-Psiquiatria. All rights reserved.The psychologist, Alfred Binet, who worked under the supervision of Prof. Charcot at the end of the 19th century, made several important contributions to neuropsychology, in partnership with Théodore Simon. Most notable among these was the development of intelligence testing scales.